Drivers of aquatic macroinvertebrate communities in a Ramsar declared wetland system - Dalu, Tatenda; Cuthbert, Ross N.; Methi, Mathapelo J.; Dondofema, Farai; Chari, Lenin D.; Wasserman, Ryan J. (The Science of the total environment, 2022)
Wetlands in the Global South are under increasing pressure due to multiple stressors associated with global change. Water and sediment quality assessments, as well as biomonitoring using macroinvertebrate communities, are fundamental tools for informing wetland condition and management strategies. Here, we examine water and sediment parameters affecting aquatic macroinvertebrates in Nlyslvey Wetland, Limpopo Province, South Africa. Water quality, sediments, fish and macroinvertebrate community data were collected across three seasons (hot-dry, hot-wet, cool-dry) from five sites. Baetidae, Corixidae, Coenogrionidae, Dytiscidae and Physidae were the most abundant and dominant families, with functional feeding group (FFG) ratios indicating that all sites were strongly autotrophic, had high predator-prey ratios, few shredders and had a stable substrate across seasons. Fish abundances increased significantly towards the cool-dry season. Based on redundancy analysis, P, Ca, pH, Cu and Na were strongly positively associated with macroinvertebrates, including Physidae, Corixidae, Planorbidae, Ostracoda, Potamonautidae and Hydropyschidae; turbidity and sulphur were associated with Dytiscidae, Oligochaetae, Libellulidae, Gerridae and Dixidae; and fish abundance, Fe, oxygen reduction potential and total dissolved solids were negatively associated with Baetidae, Belostomatidae, Hydrophilidae and Leptoceridae. Therefore, these variables accounted for high levels of variation in macroinvertebrate families, with the cool-dry season clearly distinguished from the hot-wet and hot-dry seasons according to functional feeding groups. Being a protected area, this information could provide a useful baseline for further studies into wetlands in the region subject to greater anthropogenic stresses, as well as future studies in this Ramsar site. Further studies are required to assess the importance of environmental factors influencing the richness and distribution of macroinvertebrate communities in wetlands under growing anthropogenic pressures. [Display omitted] •Baetidae, Corixidae, Coenogrionidae, Dytiscidae and Physidae were the most abundant families.•Functional feeding group ratios indicated that all sites were strongly autotrophic.•Environmental variables and fish had an influence on macroinvertebrate community.•Different macroinvertebrate taxa respond differently to seasonal changes.